Two Decades of Global Progress in Authorized Advanced Therapy Medicinal Products: An Emerging Revolution in Therapeutic Strategies - Ramezankhani, Roya; Torabi, Shukoofeh; Minaei, Neda; Madani, Hoda; Rezaeiani, Siamak; Hassani, Seyedeh Nafiseh; Gee, Adrian P.; Dominici, Massimo; Silva, Daniela Nascimento; Baharvand, Hossein; Hajizadeh-Saffar, Ensiyeh (Frontiers in Cell and Developmental Biology, 2020)
The introduction of advanced therapy medicinal products (ATMPs) to the global pharma market has been revolutionizing the field of cell and gene therapies in terms of opening new routes for treatment of various types of cancers and incurable diseases and progressively have been devoted noticeable part of clinical practices, in the past two decades. By taking into consideration the cell, gene, and tissue engineering-based products that have been approved by different regulatory agencies, in this paper, we intend to introduce and classify these approved products along with descriptions of each product, manufacturer, indication, approval date and related regulatory agency, dosage, description, and price. A summary of the available related clinical trial safety and efficacy data is also provided. In addition, to gain insights about the commercial situation of each product, we have gathered accessible sale reports and market size information that pertain to some of these products.